Implementasi IMATIC (Interactive Mathematic Comic) berbasis VBA-Excel pada materi matematika SMP untuk kemampuan literasi dan numerasi calon guru matematika di era society 5.0 - Pertiwi, Citra Megiana; Rosyana, Tina; Supardi, Alfi Fani; Al Mawaddah, Azkia Mudrikah (IKIP Siliwangi, 2023)
Era Society 5.0 which has a significant impact on various aspects, including education. Era Society 5.0 must have faced by producing competent and globally competitive human resources. Mathematics teachers candidate need to be provided with literacy skills so that it makes them easier to understand and process the information obtained to solve problems as well as numeracy skills to develop knowledge and skills to use mathematics confidently in all aspects of life. To answer these challenges, it is necessary to implement learning media, namely IMATIC (Interactive Mathematic Comic) based on VBA-Excel which is interesting, simple, educative and easy to understand. The research method uses descriptive research with test instruments, questionnaires and interviews. The results of the study show that the implementation of IMATIC can make mathematics teachers candidate have good literacy and numeracy skills. In addition, it is effectively used in learning because they understand the material by being carried away in the story so that it is easy to understand.